UJI KINERJA ALAT PEMBUAT ASAP CAIR TEMPURUNG KELAPA TIPE PIROLISIS - Adhiyanto D. Sinadia; Dedie Tooy; Freeke Pangkerego (Universitas Sam Ratulangi, 2018)
Abstract This study uses two liquid smoke makers, liquid smoke 1 and liquid smoke 2, with different sizes of volumes of pyrolysis tubes and condenser drums. The volume of the liquid smoke pyrolysis tube 1 was 753,600 cm³ and the condenser drum was 392,500 cm³, while the volume of the liquid smoke pyrolysis tube 2 was 367. 380 cm³ and the volume of the condenser drum was 196. 250 cm³. The purpose of this study is to technically test the performance of the liquid smoke maker 1 and the liquid smoke maker 2 and the rendement of liquid smoke, tar and combustion chamber temperatures during the pyrolysis process. The research method used was an experimental method and analyzed descriptively. The results of the study obtained a liquid smoke yield in liquid smoke 1 by 7.5%, a yield of 0.86% tar and a coconut shell yield of 23%. In liquid smoke tools 2 the liquid smoke yield obtained by 20%, the yield of tar 0.76% and the yield of coconut shell by 27%. The performance of the liquid smoke 1 tool is 0.375 kg / hour, while the performance of the liquid smoke tool 2 is 0.6 kg / hour. The performance of the liquid smoke tool 2 is higher than the liquid smoke tool 1. Keywords : Liquid smoke, tar, coconut shell, performance, yield, pyrolysis